Arbitrary settling time control with prescribed performance for high‐order nonlinear systems. Issue 3 (25th August 2022) - Qi, Xuelei; Ma, Hongjun; Jing, Yuanwei
Abstract: This paper studies an arbitrary convergence time tracking controller design problem for high‐order nonlinear systems. Our aim is to enhance the existing free‐will arbitrary time control (FATC), which cannot track time‐varying reference signals. To do so, a new nonautonomous equation is firstly introduced to enable an arbitrary settling time stability for one‐order systems. Then, a prescribed performance control (PPC) technology is integrated for general high order systems. By a backstepping Lyapunov analysis with iteratively contructed nonautonomous equations, it is proved that the closed‐loop system satisfies the prescribed performance and all signals of the closed‐loop system are arbitrary settling time stable (ASTS). Compared with the existing results, the tracking control problem with arbitrary convergence time is addressed by a continuous control law, which shows a better transient performance also. Simulation results confirm the effectiveness of the proposed control method.